Discovery of Lignans from the Herbs of Peperomia heyneana with Inhibitory Activities on BPH-1 Cells - Yufei Xi; Juan Liu; Congcong Gao; Mingxuan Zhu; Baomin Feng; Xuan Lu (Molecules)
Chemical investigation on the whole herb of Peperomia heyneana Miq. resulted in the isolation of six lignans, including two previously undescribed compounds, named peperomianan A and B (1–2), and four known compounds, 1,2-cyclobutanedicarboxylic acid (3), (+)-medioresinol (4), (+)-pinoresinol (5), and (+)-yangambin (6). Their structures were established by extensive spectroscopic analyses. The absolute configuration of compound 1 was determined by comparison of the experimental and calculated electronic circular dichroism (ECD) spectra. Subsequently, the effects of all isolates on BPH-1 cells were evaluated in vitro by MTT assay.